2020
DOI: 10.3390/app10124129
|View full text |Cite
|
Sign up to set email alerts
|

Municipal Solid Waste Incineration Bottom Ash as Sole Precursor in the Alkali-Activated Binder Formulation

Abstract: The concern about the large amount of weathered bottom ash (WBA) produced in waste-to-energy plants (WtE) has caused an increased search for alternatives to reduce their environmental impact. The present study aims to provide an added value through the WBA valorization from municipal solid waste incineration (MSWI) for its use as a sole precursor for developing alkali-activated binders (AABs). Alkali-activated weathered bottom ash binders (AA-WBA) were formulated with a liquid-to-solid ratio of 1.0 and using s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 56 publications
(78 reference statements)
0
17
0
1
Order By: Relevance
“…In the case of these elements, As, Se, and Mo, the natural pH of the material in the equilibrium test, around 12, coincides with the range of the greatest leaching, for that reason they are the elements that are closest to or exceed the leaching limits for non-hazardous waste landfill [51,52].…”
Section: Ph Dependence Leaching Behaviormentioning
confidence: 88%
See 1 more Smart Citation
“…In the case of these elements, As, Se, and Mo, the natural pH of the material in the equilibrium test, around 12, coincides with the range of the greatest leaching, for that reason they are the elements that are closest to or exceed the leaching limits for non-hazardous waste landfill [51,52].…”
Section: Ph Dependence Leaching Behaviormentioning
confidence: 88%
“…This means that for both elements, the concentration in the leachate exceeds the limit of the regulations for non-hazardous landfill [26]. Although the leaching of As is a fact that is described in several environmental studies of flay ash or clay based geopolymers [23,[49][50][51][52], authors who introduce EAFD for their immobilization, do not monitor this element, only those associated with the steel dust (Zn, Pb, Cr, Cd) [16,17,37]. This also occurs with other authors who use geopolymers to immobilize another hazardous waste, [34,39,53,54] none of which studies the behavior of arsenic.…”
Section: Mobilization and Availability Of Metalsmentioning
confidence: 99%
“…Furthermore, novel applications have been explored for this material. For example, its use as a precursor for alkali-activated binders, as adsorbent material to remove contaminants from wastewater and landfill gases, and as raw material for the production of ceramic-based products [40,59,89,90].…”
Section: Iba Production and Characterizationmentioning
confidence: 99%
“…The study showed that the valorization of steel and aluminum recovered from IBA enables great energy savings in the steel and aluminum industries, which are energy-intensive sectors. Moreover, the utilization of IBA to produce cement reduced the consumption of natural resources [90,119,120]. Silva et al [11] provided a literature review regarding the environmental performance of the utilization of IBA in construction-related products.…”
Section: Potential Drivers Barriers and Prospects For Iba Usementioning
confidence: 99%
“…IBA is mainly composed of Si, Al, Ca, and Na oxides, and could be classified as a hazardous or non-hazardous waste depending on the amount of toxic metal(oid)s. IBA's main applications are in the engineering field as secondary materials in form of weathered bottom ash (after outdoor ageing for 2-3 months for pH stabilization). However, new applications of IBA have emerged in recent years as use as an aluminosilicate source for GPs/AAMs [17] including adsorbents [15,[18][19][20]. IBA by itself also was investigated as an adsorptive material for metal removal [21,22].…”
Section: Raw Materials and Preparation Of Gp/aam Materials For Water mentioning
confidence: 99%